Time, space and situations in an internet bulletin board service - Dell, Peter (IADIS press, 2010)
The definition of situations proposed by Joshua Meyowitz is examined in the light of computer-mediated communication (CMC), and refined for this environment. It is concluded that for situations to be useful in analysing behaviour in public places created within CMC, a definition of situations as information access patterns is too broad. Instead, a definition that recognises such flows of information between situations is required. Goffman's definition, based on temporal and spatial boundaries, can be used if one takes into account the creation of virtual space. This approach is demonstrated in analysis of an Internet Bulletin Board Service.